2014
DOI: 10.1007/s40167-014-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Uyghur-Chinese and Han-Chinese differences on social orientation

Abstract: In two studies, the authors predicted and found that Uyghur-Chinese are more independent and interdependent than Han-Chinese in explicit and implicit measurements: (a) Uyghur-Chinese are more independent in explicit beliefs and show strong dispositional bias and express more socially disengaging emotion and more relational mobility. Their independence could partially mediate the relationship between culture and dispositional bias and socially disengaging emotion and relational mobility. (b) At the same time, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…Previous studies have identified differences in social orientations between different ethnic groups, i.e., the Uyghur and Han Chinese (Ren et al, 2014) and between Northern and Southern Chinese , which was consistent with our results. We assume the differences observed in the current study are related to the fact that the Mongolian have traditionally been known as nomadic herders (Li and Huntsinger, 2011;Wang et al, 2013), while the Han Chinese have been known as traditional agrarian community .…”
Section: Ecological Systemssupporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies have identified differences in social orientations between different ethnic groups, i.e., the Uyghur and Han Chinese (Ren et al, 2014) and between Northern and Southern Chinese , which was consistent with our results. We assume the differences observed in the current study are related to the fact that the Mongolian have traditionally been known as nomadic herders (Li and Huntsinger, 2011;Wang et al, 2013), while the Han Chinese have been known as traditional agrarian community .…”
Section: Ecological Systemssupporting
confidence: 93%
“…According to Uskul et al (2008), exploring variations in cognitive tendencies within an environment with shared identity, ethnicity, or language in relation to variations in social orientations is extremely useful; it allows for enhanced control over a potentially large number of confounding variables (Uskul et al, 2008). This premise has been confirmed by several studies that reported differences between the Uyghur Chinese and Han Chinese in terms of social orientation (Ren et al, 2014), as well as the Hokkaido Japanese and mainland Japanese, where the former were more independent and showed more dispositional bias in attribution (Kitayama et al, 2006). Furthermore, Northern Italians have been shown to be more independent than Southern Italians (Martella and Maass, 2000), and neighboring villages in Turkey were observed to diverge in terms of individual/interdependent orientations based on their main economic activities (Uskul et al, 2008).…”
Section: Social Interdependence and Independencementioning
confidence: 96%
See 2 more Smart Citations
“…Evidence for collectivism differences between Region I and the other regions has mainly come from studies comparing Uyghur, Tibetan, and Mongolian ethnic groups with Han groups. Ren et al (2014) found that Uyghur Chinese exhibited both high individualism and high collectivism in self-report questionnaires, attribution, relational mobility, social engaging/ disengaging emotions, and other tasks compared with Han Chinese. Mamat et al (2014, Study 2) found that Uyghur Chinese were lower in relational self than Han Chinese using a self-reference paradigm task.…”
Section: Evidence Supporting the Triple-line Frameworkmentioning
confidence: 94%